On fair and efficient bandwidth sharing in user provided networks - (:unkn) unknown (IEEE Computer Society, 2019)
Since the first introduction of User Provided Networks (UPNs), considerable effort has been put into designing incentive mechanisms as one of the backing techniques needed to realize them. Concepts especially from game theory can be identified as the core building blocks of contemporary incentive mechanisms proposed in the literature. In this work a collaborative Internet sharing mechanism from a potential game theoretical point of view has been proposed while keeping simplicity, applicability in real world scenarios in mind. The proposed scheme supports multi-node deployments and favors fair bandwidth sharing among players as well as providing effective usage of globally available bandwidth. The proposed scheme converges to a Nash equilibrium in pure strategies, when played in best reply dynamics. In order to evaluate its performance it is compared to another scheme which is supposed to admit players' available bandwidth as its potential function. The second scheme has been investigated by rigorous simulations and shown to converge to a Nash equilibrium in pure strategies, although it still lacks an analytical demonstration to be proven as a potential game. Results show that as well as supporting multi-node deployments, the proposed scheme also fairly distributes the available bandwidth among players and increases the globally available bandwidth being shared. © 2019 IEEE.
Keywords: bandwidth sharing; incentive design; User provided networks